Selective Regulation of Osteoblastic OPG and RANKL by Dehydroepiandrosterone Through Activation of the Estrogen Receptor β-mediated MAPK Signaling Pathway - Wang, Y.-D.; Tao, M.-F.; Wang, L.; Cheng, W.-W.; Wan, X.-P. (Hormone and Metabolic Research, 2012)
The aim of the work was to investigate the differential regulation by dehydroepiandrosterone (DHEA) of the osteoblastic production via the estrogen receptor beta (ER β)-mediated signaling pathway. Having developed hMG63-ER β cells and hMG63-shER β cells, we analyzed the regulation by DHEA of human osteoblastic viability, the receptor activator of nuclear factor kappa-B ligand (RANKL), osteoprotegerin (OPG), and the differential expression of ER β, ER α, or p-ERK1/2 (extracellular signal-regulated kinase) in hMG63, hMG63-shER β, and hMG63-ER β cells pretreated with or without U0126, flutamide, and ICI 182780, followed by DHEA culture. When the level of ER β was high, DHEA (10 − 7  mol/l) could effectively amplify the proliferation and inhibit the etoposide-induced apoptosis of hMG63 cells (p<0.01 and p<0.05, respectively), which was blocked by U0126. When the expression of ER β was silenced, DHEA could not significantly improve the viability of hMG63. In the presence of ER β, DHEA activated the pERK1/2-MAPK signaling pathway but not p38 and JNK. Besides, the regulation of p-ERK1/2 upon DHEA treatment was mainly modulated by ER β instead of androgen receptor and ER α. The secretion of OPG was declined following the silence of ER β (p<0.05). RANKL and ER α, however, were unaffected by culture with or without DHEA and U0126, regardless of the ER β level. DHEA seems to act selectively on osteoblasts via the dominant ER β receptor, which mediates amplified cell viability through the MAPK signaling pathway involving pERK1/2 and upregulates the production of OPG rather than RANKL.
Keywords: dehydroepiandrosterone; estrogen receptor β; OPG; RANKL